No reduction in instrumental vaginal births and no increased risk for adverse perineal outcome in nulliparous women giving birth on a birth seat: results of a Swedish randomized controlled trial - Christensson Kyllike; Kvist Linda J; Thies-Lagergren Li; Hildingsson Ingegerd (BMC, 2011)
Abstract Background The WHO advises against recumbent or supine position for longer periods during labour and birth and states that caregivers should encourage and support the woman to take the position in which she feels most comfortable. It has been suggested that upright positions may improve childbirth outcomes and reduce the risk for instrumental delivery; however RCTs of interventions to encourage upright positions are scarce. The aim of this study was to test, by means of a randomized controlled trial, the hypothesis that the use of a birthing seat during the second stage of labor, for healthy nulliparous women, decreases the number of instrumentally assisted births and may thus counterbalance any increase in perineal trauma and blood loss. Methods A randomized controlled trial in Sweden where 1002 women were randomized to birth on a birth seat (experimental group) or birth in any other position (control group). Data were collected between November 2006 and July 2009. The primary outcome measurement was the number of instrumental deliveries. Secondary outcome measurements included perineal lacerations, perineal edema, maternal blood loss and hemoglobin. Analysis was by intention to treat. Results The main findings of this study were that birth on the birth seat did not reduce the number of instrumental vaginal births, there was an increase in blood loss between 500 ml and 1000 ml in women who gave birth on the seat but no increase in bleeding over 1000 ml and no increase in perineal lacerations or perineal edema. Conclusions The birth seat did not reduce the number of instrumental vaginal births. The study confirmed an increased blood loss 500 ml - 1000 ml but not over 1000 ml for women giving birth on the seat. Giving birth on a birth seat caused no adverse consequences for perineal outcomes and may even be protective against episiotomies. Trial registration number ClinicalTrials.gov.ID: NCT01182038